Uncovering Molecular Heterogeneity in the Kidney With Spatially Targeted Mass Spectrometry - Kruse, Angela R. S.; Spraggins, Jeffrey M. (Frontiers in Physiology, 2022)
The kidney functions through the coordination of approximately one million multifunctional nephrons in 3-dimensional space. Molecular understanding of the kidney has relied on transcriptomic, proteomic, and metabolomic analyses of kidney homogenate, but these approaches do not resolve cellular identity and spatial context. Mass spectrometry analysis of isolated cells retains cellular identity but not information regarding its cellular neighborhood and extracellular matrix. Spatially targeted mass spectrometry is uniquely suited to molecularly characterize kidney tissue while retaining in situ cellular context. This review summarizes advances in methodology and technology for spatially-targeted mass spectrometry analysis of kidney tissue. Profiling technologies such as laser capture microdissection (LCM) coupled to liquid chromatography-tandem mass spectrometry provide deep molecular coverage off specific tissue regions, while imaging technologies such as matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI IMS) map molecular distributions with greater spatial resolution. These technologies individually have furthered our understanding of heterogeneity in nephron regions such as glomeruli and proximal tubules, and their integration with orthogonal biomolecular imaging technologies is expected to profoundly expand our knowledge of the kidney in health and disease.